PUBLICLY FUNDED MEDICAL TRAVEL SUBSIDY PROGRAMS IN CANADA - Mathews, Maria; Ryan, Dana (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2017)
Rural residents can incur substantial travel-related costs to receive needed care. In this study, we describe and compare the medical travel programs offered by provincial and territorial governments. We conducted a document analysis of medical travel subsidy programs available in Canada to the general public. Only programs funded and administered by provincial/territorial governments were included. Based on the information that we collected, we determined there were three types of programs. Discount programs (BC) allow eligible patients to receive reduced or waived prices for travel and lodging at designated providers. Non-reimbursement programs (BC, SK) cover the costs of travel and lodging without requiring patients to pay for costs up-front. In reimbursement programs (MB, ON, QC, PEI, NS, NL, YK, NWT, NT), patients generally pay costs up-front and then submit claims for reimbursement after receiving the health service. Rates, co-payments, and maximum allowable amounts vary by program. Our findings indicated that although many provinces and territories offer medical travel subsidy programs, the availability, terms, and conditions vary widely. The study highlights regional disparities that may contribute to inequitable access to care across Canada.